Plurinational Constitutionalism: A New Era of Indigenous-State Relations? - Schilling-Vacaflor, Almut; Kuppe, René (Taylor and Francis, 2016)
The increasing recognition of group rights and cultural diversity has been one of the main characteristics of modern constitutionalism worldwide since the second half of the twentieth century (Lutz 2001). Generally, it has been intertwined with the adoption of longer and more complex bills of rights, most recently judicable social rights (see Sunstein 2001: 221). In Latin America, ‘multi-ethnic constitutionalism’ has spread since 1978 with the third wave of democratization (Van Cott 2000, Yrigoyen 2010). The rights of indigenous peoples and, more recently, of inhabitants of African descent in particular have been enshrined in the constitutions of the region.1.
CRIS-Team Scopus Importer:2023-11-20